2014
DOI: 10.1177/1523422313520476
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Coaching

Abstract: The Problem While managerial coaching becomes increasingly popular in both scholarly and practical circles, the line managers who need to execute this coaching may be neither capable nor interested in the coaching process. Furthermore, while the research on coaching seems promising, little is known about how to test the individual and environmental appropriateness of a coaching intervention. The Solution This review will inform and support evidence-based human resource development (HRD) professionals tasked wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 25 publications
1
61
0
1
Order By: Relevance
“…Managerial coaching attained considerable attention in the field of business and management [28,41,42] as a powerful tool for influencing employees' attitudes and behaviors [36,[43][44][45]. Managerial coaching refers to the actions of the manager or leader who acts as a coach and facilitates learning in the workplace environment through specific behaviors that enable the employee to learn and develop [37].…”
Section: Managerial Coachingmentioning
confidence: 99%
See 2 more Smart Citations
“…Managerial coaching attained considerable attention in the field of business and management [28,41,42] as a powerful tool for influencing employees' attitudes and behaviors [36,[43][44][45]. Managerial coaching refers to the actions of the manager or leader who acts as a coach and facilitates learning in the workplace environment through specific behaviors that enable the employee to learn and develop [37].…”
Section: Managerial Coachingmentioning
confidence: 99%
“…Managerial coaching refers to the actions of the manager or leader who acts as a coach and facilitates learning in the workplace environment through specific behaviors that enable the employee to learn and develop [37]. It was found that this management is related to several organizational outcomes such as improving performance [37,43,[46][47][48], self-efficacy [48], innovative work behavior [46], satisfaction [43,44,49], extra-role performance, organizational commitment [39], role clarity [44,46,49,50], goal accomplishment, trustworthiness, learning [3,28,[51][52][53], psychological empowerment [46], proactive career behaviors, well-being, resilience [54], and decreased turnover intention [39].…”
Section: Managerial Coachingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the extant literature on managerial coaching (e.g., Beattie et al, 2014;Hagen, 2012) has indicated that employees' trust in supervisors could play an important role in an effective coach-coachee relationship, and might determine the effectiveness of managerial coaching. As MCSs have been discussed together with employees' trust in supervisors (Beattie et al, 2014;Kim & Kuo, 2015), and previous studies have established the relationship between employees' trust in supervisors and their FSB (Choi, Moon, & Nae, 2014;Hays & Williams, 2011), it is likely that trust in supervisors works as a potential intervening mechanism linking MCSs to employee IMFSB.…”
mentioning
confidence: 99%
“…In addition, the extant literature on managerial coaching (e.g., Beattie et al, 2014;Hagen, 2012) has indicated that employees' trust in supervisors could play an important role in an effective coach-coachee relationship, and might determine the effectiveness of managerial coaching. As MCSs have been discussed together with employees' trust in supervisors (Beattie et al, 2014;Kim & Kuo, 2015), and previous studies have established the relationship between employees' trust in supervisors and their FSB (Choi, Moon, & Nae, 2014;Hays & Williams, 2011), it is likely that trust in supervisors works as a potential intervening mechanism linking MCSs to employee IMFSB. When examining trust in supervisors as a intervening variable, we focus our attention on the role of affective trust, defined as the emotional bonds between individuals that are grounded upon expressions of genuine care and concern for the welfare of the other party (McAllister, 1995), because it is social exchange and more relational in nature (Dirks & Ferrin, 2002) and can be a critical component to constitute the effective exchange relationship in a managerial coaching context (Kim & Kuo, 2015).…”
mentioning
confidence: 99%